The impact of an innovative pharmacist-led inpatient opioid de-escalation intervention in post-operative orthopedic patients - Bui, BPharm, Thuy; Grygiel, MPharm, Richard; Konstantatos, MB BS (Hons), FANZCA, Dip Obs, MRCA, Alex; Christelis, Nick; Liew, MB BS (Hons), FRACS, Susan; Hopkins, BHSci (Hons), MPH, Ria; Dooley, BPharm, Grad DipHospPharm, PhD, Michael (Journal of Opioid Management, 2020)
Objective: Many patients are discharged from hospital after surgery with excessive doses of opioid, and prescription opioid addiction has become a serious public health problem. Inpatient opioid de-escalation performed by clinical pharmacists may assist in reducing opioids before discharge. We aimed to evaluate whether clinical pharmacist-led opioid de-escalation for inpatients after orthopedic surgery led to significant reductions in opioid use at discharge, without resulting in greater pain intensity and side effects. Design: This retrospective pre-/post-intervention study evaluated patients before and after implementation of a pharmacist-led opioid de-escalation service. Setting: A major tertiary institution. Participants: Ninety eight participants underwent de-escalation, and 98 controls received standard care following orthopedic surgery. Intervention: Pharmacist-led opioid de-escalation was initiated after discharge from the institution’s Acute Pain Service. Main outcome measure: Primary outcome was total morphine oral equivalence (MOE) required in the 24-hours before discharge between the two groups. Secondary outcomes included pain intensity scores and opioid-related side effects. Results: The post-intervention group used significantly less opioids in the 24 hours preceding discharge compared with the precohort (total MOE 30 vs 45 mg; p = 0.025).There were no differences in pain intensity at rest (p = 0.19) or with movement (p = 0.19). Cases experienced significantly less constipation (29 vs 49 percent; p = 0.004); no differences were observed for other side effects. Discussion: We observed statistically similar pain intensity ratings, in the setting of significantly lowered opioid doses among the post-intervention group prior to discharge. Conclusion: Pharmacist-led inpatient opioid de-escalation is effective, does not increase pain intensity, and reduces constipation. Hospitals should explore the viability of extending pharmacist-led opioid de-escalation to other surgical patients and following hospital discharge, aiming for opioid cessation.